2017
DOI: 10.1021/acs.jmedchem.7b01290
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Optimization of Pyrrolopyrimidine Inhibitors of Interleukin-1 Receptor Associated Kinase 4 (IRAK4) for the Treatment of Mutant MYD88L265P Diffuse Large B-Cell Lymphoma

Abstract: Herein we report the optimization of a series of pyrrolopyrimidine inhibitors of interleukin-1 receptor associated kinase 4 (IRAK4) using X-ray crystal structures and structure based design to identify and optimize our scaffold. Compound 28 demonstrated a favorable physicochemical and kinase selectivity profile and was identified as a promising in vivo tool with which to explore the role of IRAK4 inhibition in the treatment of mutant MYD88 diffuse large B-cell lymphoma (DLBCL). Compound 28 was shown to be capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 46 publications
4
31
1
Order By: Relevance
“…Further evidence for this comes from a recent study that demonstrated that phosphorylation and ubiquitylation of IRAK1 may simply be due to Myddosome‐induced formation of IRAK1 dimers, rather than as a substrate of IRAK4 . Hence, understanding scaffolding versus enzymatic roles, including the genuine substrates of the IRAKs, is of fundamental importance to our understanding of early TLR signaling and may lead to a revaluation of the current therapeutic strategies targeting the kinase activity of the IRAKs . Recently, an interesting drug screening approach identified a novel compound that directly disrupts MyD88 oligomerization and subsequently TLR4‐induced cytokine secretion in vivo suggesting that blocking the scaffolding function of Myddosome components may provide a better therapeutic option …”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for this comes from a recent study that demonstrated that phosphorylation and ubiquitylation of IRAK1 may simply be due to Myddosome‐induced formation of IRAK1 dimers, rather than as a substrate of IRAK4 . Hence, understanding scaffolding versus enzymatic roles, including the genuine substrates of the IRAKs, is of fundamental importance to our understanding of early TLR signaling and may lead to a revaluation of the current therapeutic strategies targeting the kinase activity of the IRAKs . Recently, an interesting drug screening approach identified a novel compound that directly disrupts MyD88 oligomerization and subsequently TLR4‐induced cytokine secretion in vivo suggesting that blocking the scaffolding function of Myddosome components may provide a better therapeutic option …”
Section: Discussionmentioning
confidence: 99%
“…A range of recent structure-based drug discovery case studies demonstrate the power of nuclear magnetic resonance (NMR) conformational analysis to elucidate SAR trends with respect to conformational preferences of the free ligand [4][5][6][7][8][9][10][11][12][13][14]. In the majority of cases, knowledge of the free ligand conformational preference clearly aided structure-based design.…”
mentioning
confidence: 99%
“…In addition, mutations in CD79B, MYD88 , and TBL1XR1 leading to abnormal NF-kB signalling activation may result in the lymphomagenesis of PC-DLBCL and serve as therapeutic targets 6. The novel targeted therapy drugs, including inhibitors of BTK, SYK, PKC, IRAK1/4 and PIM, could be replacement selections 2427…”
Section: Discussionmentioning
confidence: 99%